2014
DOI: 10.1016/j.sbspro.2014.12.346
|View full text |Cite
|
Sign up to set email alerts
|

Personality, Family Correlates and Emotion Regulation as Wellbeing Predictors

Abstract: This research integrates three concepts (personality, family correlates and emotion regulation) in a predictive model of wellbeing. We measured the impact of the personality structure, the adult attachment style, the style for socializing internalizing and externalizing emotions and the emotion regulation strategies (cognitive reappraisal, expressive suppression) on general wellbeing. A set of eight self-administered scales were filled up by 516 subjects, aged between 14 and 34 (M = 18.62; SD = 3.32). The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…When it comes to the impacts of two types of emotional regulation on life satisfaction, the results are largely consistent with the results of exploring basic relationships (e.g., Yiğit et al, 2014). This conclusion is supported by Hua and associates in a meta-analysis study (Hu, Zhang, & Wang, 2015), but there are also findings on the absence of these effects (Liliana & Nicoleta, 2014).…”
Section: Satisfaction With Life and Emotion Regulation: Operationalizsupporting
confidence: 83%
“…When it comes to the impacts of two types of emotional regulation on life satisfaction, the results are largely consistent with the results of exploring basic relationships (e.g., Yiğit et al, 2014). This conclusion is supported by Hua and associates in a meta-analysis study (Hu, Zhang, & Wang, 2015), but there are also findings on the absence of these effects (Liliana & Nicoleta, 2014).…”
Section: Satisfaction With Life and Emotion Regulation: Operationalizsupporting
confidence: 83%
“…It involves emotions like anxiety, worry, sadness and tension. Liliana and Nicoleta (2014) showed that emotional stability predicted well-being on all four dimensions: positive affects, negative affects, emotional distress and life satisfaction. Emotion regulation strategies are predictors for (positive and negative) affects only, and not for emotional distress or life satisfaction.…”
Section: Discussionmentioning
confidence: 98%
“…Emotion regulation is.a cognitive reappraisal strategy to forward aversive emotional reduce the negative and social consequences (Gross, 1998;Matsumoto, Nakagawa, & Sanae, 2008;Volokov, 2008). Liliana and Nicoleta (2014) founded that emotional stability predicts wellbeing on all four dimensions: positive affects, negative affects, emotional distress and life satisfaction. Emotion regulation strategies are predictors for (positive and negative) affects only, and not for emotional distress or life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…The dimensions of empathy that were evaluated by the new instrument were therefore hypothesized to have a positive relationship with prosociality and a negative relationship with physical and verbal aggression. Moreover, evidence exists about a negative relationship between emotional instability and the dimension of emotional regulation (Singh and Mishra, 2011; Khosla, 2012; Bujor and Turliuc, 2014). Thus, a negative relationship between these constructs was hypothesized.…”
Section: Instrument Studymentioning
confidence: 99%